Effect of pilose antler polypeptide on the mechanism of bone homeostasis in osteoporosis - Wang, Guochen; Meng, Yubo; Ouyang, Wensi; Zhao, Changwei; Zhao, Wenhai (Frontiers in Medicine, 2023)
Osteoporosis stands out as a prevalent metabolic disorder, bearing significant repercussions on human well-being and overall quality of life. It remains an urgent concern within the global public health framework due to its widespread occurrence. Osteoporosis arises from an abnormal metabolism in osteoblasts and osteoclasts, resulting in a disruption of the delicate equilibrium between bone formation and bone resorption. Within this context, deer antler peptides emerge as natural active compounds, wielding a pivotal role in governing the differentiation, proliferation, and mineralization of osteoblasts, as well as influencing the activity of osteoclasts. This article aims to consolidate our comprehension of the mechanisms underpinning the dynamic balance between bone formation and resorption, meticulously orchestrated by osteoblasts and osteoclasts in osteoporosis. Furthermore, it offers a comprehensive overview of how deer antler peptides, through their modulation of relevant signaling pathways, contribute to the enhancement of bone homeostasis. These insights deepen our understanding of the pathological processes through which deer antler peptides ameliorate bone homeostasis, while also presenting novel strategies for osteoporosis management.